Optical edge projection for surface contouring - Wu, X. P. (2010)
A novel optical edge projection method is proposed for surface contouring of an object with low reflectivity. A structured light edge is projected onto a dark surface, and the image is captured by a CCD camera. The object contour is evaluated using active triangular projection algorithm, and a whole field 3D contour of the object is obtained by scanning the optical edge over the entire object surface. The proposed method is applied to a black low-reflective object made of weaved carbon fiber. The results which are verified with conventional phase shifting fringe projection technique show that an accurate profile of a specimen can be obtained. The proposed method is also applied to surface contouring of a small component.